Réponses

2013-04-07T13:22:06+02:00

Bonjour,

 

Utilise les identités remarquables :

(4x+3)^2-1 = 0\\ \left[(4x+3)-1\right]\left[(4x+3)+1\right] = 0\\ (4x+2)(4x+4) = 0\\ 2(2x+1)\times 4(x+1) = 0\\ 8(2x+1)(x+1) = 0\\

 

Donc on a :

2x+1=0\\ 2x = -1\\ x = -\frac 12

Ou bien :

x+1 = 0\\ x = -1

 

On écrit donc :

S = \left\{-\frac 12 ; -1\right\}

 

De la même façon, pour l'autre équation :

(2x+5)^2-x^2 = 0\\ \left[(2x+5)+x\right]\left[(2x+5)-x\right] = 0\\ (3x+5)(x+5) = 0\\ S = \left\{-\frac 53 ; -5\right\}